Wie schneiden die großen ostdeutschen Städte im gesamtdeutschen Vergleich ab? Daten zu ihrer wirtschaftlichen und finanziellen Lage - Franz, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
In this article the 13 largest East German cities (without Berlin) are compared with cities of similar size in three West German regions (South, Central, North) with respect to their economic and financial situation. The indicators show a differentiated picture. The GDP of the East German cities surmounts that of the Ruhr cities, but is still far below of the cities in the South. Unemployment and migration loss is most pronounced in the East German cities. Nevertheless they dispose of several favorite preconditions for growth in the future: their endowment with qualified human capital, public research and with enterprise-oriented services is above average. This contrasts with a low density of firms. The East German cities have a weak tax base and are disproportionally dependent on financial assignments by the state. Besides the East German cities the data show another “problem group” consisting of the cities of the Ruhr. The disparities between the West German Regions discovered in the 80s are still existing.